Evaluation of the bending response of compact and thin-walled FG beams with CUF. Issue 17 (2nd September 2021) - Demirbas, Munise Didem; Caliskan, Umut; Xu, Xiangyang; Filippi, Matteo
Abstract: The study deals with the stress evaluations of the functionally graded beams (FGBs) using refined beam models. The refined beam models are obtained within the framework of the Carrera unified formulation (CUF), where expansions are used across the cross-section to enrich the kinematics of the finite elements and obtain 3 D-like accuracy of the solution. Analyses of FGBs are performed by using different structural theories based on Taylor-like and Lagrange expansions. The results are compared with the literature and 3 D finite element solutions. It is observed that calculation costs are significantly decreased in finite element analyses performed with CUF.